Regulatory toxicology in the twenty-first century: challenges, perspectives and possible solutions - Tralau, Tewes; Oelgeschläger, Michael; Gürtler, Rainer; Heinemeyer, Gerhard; Herzler, Matthias; Höfer, Thomas; Itter, Heike; Kuhl, Thomas; Lange, Nikola; Lorenz, Nicole; Müller-Graf, Christine; Pabel, Ulrike; et al. (Archives of toxicology, 2015)
The advent of new testing systems and “omics”-technologies has left regulatory toxicology facing one of the biggest challenges for decades. That is the question whether and how these methods can be used for regulatory purposes. The new methods undoubtedly enable regulators to address important open questions of toxicology such as species-specific toxicity, mixture toxicity, low-dose effects, endocrine effects or nanotoxicology, while promising faster and more efficient toxicity testing with the use of less animals. Consequently, the respective assays, methods and testing strategies are subject of several research programs worldwide. On the other hand, the practical application of such tests for regulatory purposes is a matter of ongoing debate. This document summarizes key aspects of this debate in the light of the European “regulatory status quo ”, while elucidating new perspectives for regulatory toxicity testing.